Pregnancy after intracytoplasmic sperm injection following extended sperm preparation and hormone therapy in an azoospermic man with maturation arrest and microlithiasis: a case report and literature review. (29th July 2016) - Barbotin, A.‐L.; Ballot, C.; Sigala, J.; Leroy, M.; Rigot, J.‐M.; Dewailly, D.; Robin, G.; Mitchell, V.
Summary: In the management of azoospermia, a combination of testicular sperm extraction and intracytoplasmic sperm injection (ICSI) is usually the most successful option for fatherhood. However, an outstanding question remains: How can at least a few spermatozoa be obtained from the ejaculate, thus avoiding the need for a surgical procedure? A 36‐year‐old man presented to Assisted Reproduction Unit with his 26‐year‐old wife. The ultrasound assessment revealed bilateral microlithiasis. Two spermograms revealed absolute azoospermia. Levels of follicle‐stimulating hormone (FSH) and luteinising hormone were normal–low. The patient underwent 10 months of treatment with clomiphene citrate. A bilateral testicular sperm extraction failed to retrieve spermatozoa and revealed a maturation arrest at spermatocyte/spermatid stages depending on the tubules. Clomiphene citrate was replaced with recombinant FSH (rFSH). After 9‐month treatment with rFSH, motile spermatozoa from droplets of ejaculate pellet were cryopreserved as a single straw. Ovarian stimulation was provided using classic antagonist protocol, and five mature oocytes were collected. Two consecutive fresh semen samples on the day of ICSI yielded seven motile spermatozoa, and fertilisation was achieved in all five oocytes. On day 3, two embryos were transferred, yielding positive beta‐human chorionic gonadotropin and a healthy delivery of a boy and a girl.